Product development specifications for a follicular sampling device for use in a human in-vitro fertilisation clinic : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Bioprocess Engineering at Massey University, Palmerston North, New Zealand - Harding, Hamish Alexander (Massey University, 2005)
The likelihood of pregnancy in human in-vitro fertilisation is heavily dependent on the condition of the embryos that are re-implanted into the patient's uterus. The condition of embryos is in turn dependent on the quality of the oocytes, from which they grew. It has been suggested previously that oocyte quality could be related to the level of dissolved oxygen in the ovarian follicle. The first objective of this work was to develop a set of product development specifications for a device that would be used routinely in a fertility clinic for sampling follicular fluid for dissolved oxygen determination. The second objective was to design and construct a prototype so that the relationship between dissolved oxygen and oocyte quality could be established. A length of time was spent at two fertility clinics, one in Hamilton, New Zealand and one in Auckland, New Zealand. The experiences at these clinics, as well as technical constraints, were translated into a set of product development specifications. These specifications canvassed issues relating to cleanliness, potential damage to the oocyte and preservation of the dissolved gas equilibrium in the sample. A prototype device was designed and developed and found to be wanting in the clinical environment. Further clinical constraints were identified from this experience, allowing a second prototype device to be developed. This second device was found to be suitable for clinical use and it is anticipate that in the future the sampling device will re-emerge in a new, more suitable form, based on the specifications developed in this thesis. Measurements of intra-follicular dissolved oxygen are on-going.
Keywords: Fertilization in vitro, Human; Equipment and supplies; Human reproductive technology